Silencing of PD-1 combined with EBV-specific killer T cells for the treatment of EBV-associated B lymphoma - Jiaping Wang; Zhijuan Xu; Yanli Lai; Yanli Zhang; Ping Zhang; Qitian Mu; Shujun Yang; Yongcheng Sun; Lixia Sheng; Guifang Ouyang (Translational Oncology, 2024)
Epstein-Barr Virus (EBV) infection is closely associated with the development of lymphoma, as it plays a significant role in the malignant transformation of lymphocytes. The expression of programmed death-1 (PD-1), which binds to PD-L1 in tumor cells, can lead to immune evasion by lymphoma cells and promote tumor progression. In this study, immortalized B lymphoblastoid cell lines (B-LCLs) positive for EBV-specific proteins were established from human peripheral mononuclear cells (PBMCs) using EBV induction along with CpG-ODN 2006 and cyclosporin A. EBV-specific T cells (EBVST) were generated by multiple immunizations of CD3+ T lymphocytes using irradiated B-LCLs. Flow cytometry analysis confirmed the activation of EBVST through the detection of CD3+, CD4+, and CD8+ markers. Co-incubation of EBVST with EBV-positive B lymphocyte cell lines resulted in the secretion of perforin by EBVST, leading to granzyme B-mediated cell death and an increase in LDH levels. Silencing PD-1 in EBVST cells enhanced perforin production, increased granzyme B release, and upregulated cell death in co-incubated B lymphocytes. In a nude mice tumor transplantation model, silencing PD-1 in combination with EBV-specific killer T cells exhibited the maximum inhibition of B-lymphoblastoma. This treatment upregulated the expression of proteins associated with apoptosis and immune response, while inhibiting anti-apoptotic protein expression in tumor tissues. Silencing PD-1 also increased the infiltration of EBV-specific killer T cells in the tumor tissues. Overall, PD-1 silencing enhanced the tumor targeting effect of EBV-specific killer T cells on EBV-infected B lymphocytes and attenuated the immune escape effect mediated by the PD-1 pathway.